PREVALENCE OF RISK FOR BURNOUT SYNDROME AMONG MILITARY POLICE - Rosana Amora Ascari (Cogitare Enfermagem, 2016)
This is a transversal and descriptive study with a quantitative approach, with 127 military police officers assigned to a municipality in the west of the Brazilian state of Santa Catarina. The study aimed to assess the risk of developing Burnout Syndrome among military police officers, through the use of the MaslachBurnoutInventory-Human Services Survey. The data were collected in October – December 2014. There was a prevalence of men, aged between 18 and 39 years old, with a partner, educated to degree level, without children, who did not work anywhere else,and who worked on a shift system. No individual was identified as having Burnout Syndrome and they did not have a low level of Professional Fulfillment, associated withhigh levels of Emotional Exhaustion and Depersonalization. The study evidenced that there is no incidence of the Syndrome among the police officers: however, it indicates that there is a prevalence of riskfor its development among them.